Analisis Kepuasan Konsumen Terhadap Bauran Pemasaran Di Durian Runtuh Nadhira Napoleon Pekanbaru - Fitri, Mozhalita Desta; Restuhadi, Fajar; Kurnia, Deby (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Durian Collapse tries to increase customer satisfaction with a marketing mix strategy. Customers are satisfied if Durian Collapsed's performance is higher or equal to the customer's interests. This study aims to analyze the level of consumer satisfaction, and analyze the efforts made to increase consumer satisfaction at Durian Runtuh. The research was conducted at Durian Runtuh Nadhira Napoleon at Jalan Jendral Sudirman, Simpang Tiga, Pekanbaru City. Selection of samples using convenience sampling method, with a total sample of 95 respondents. Data analysis used is the Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). The results showed that based on the Customer Statistics Index (CSI), consumers were satisfied with a score of 80.00% on Durian Runtuh's performance. Efforts made to meet consumer satisfaction are by increasing the attributes of affordable prices, prices with other competitors, promotions by giving discounts, and various promotional media.